Real time face recognition and tracking system - Baykara, Muhammet; Das, Resul (IEEE Computer Society, 2013)
Nowadays that security comes into more prominence every day, it is necessary for people to keep more passwords in their mind and carry more cards with themselves. Such implementations however, are becoming less secure and practical, thus leading to an increasing interest in techniques related to biometrics systems. Biometrics systems are the systems which store physical properties of people in electronic environment and enable them to be recognized by the stored electronic information when needed. Biometrics is the identification of human. It works on the principle of identification of physical properties of a person which he or she cannot alter, are distinctive from others, can be used for identification, and are in his or her possession only. Extensive studies are conducted on biometrics techniques such as fingerprint, hand, face, iris, retina and voice recognition. Some systems have been developed, tested, and results have been obtained. Face recognition systems are among the most important subjects in biometrics systems. These systems, which are very important for security in particular, have been widely used and developed in many countries. This study aims to achieve face recognition successfully by detecting human face in real time, based on Principal Component Analysis (PCA) algorithm and comparing the result with pre-recorded face samples. © 2013 IEEE.
2013 10th International Conference on Electronics, Computer and Computation, ICECCO 2013 -- 7 November 2013 through 8 November 2013 -- Ankara -- 102696
Keywords: Face recognition; Face tracking; Information security system; PCA; Principal component analysis